2018
DOI: 10.1080/09168451.2018.1497939
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus plantarum LRCC 5273 isolated from Kimchi ameliorates diet-induced hypercholesterolemia in C57BL/6 mice

Abstract: This study was designed to select potent cholesterol-lowering probiotic strains on HepG2 cell and investigate the effect of selected strain, Lactobacillus plantarum LRCC 5273 and LRCC 5279 in hypercholesterolemic mice. In the results, LP5273 group showed significantly reduced total and LDL cholesterol compared to HCD group. In addition to significantly up-regulated hepatic mRNA expression of LXR-α and CYP7A1, intestinal LXR-α and ABCG5 were significantly up-regulated in LP5273 group. With activation of hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
3
16
1
Order By: Relevance
“…Therefore, the expression of hepatic Cyp7A1 protein reflects the hepatic cholesterol level and the influx of bile acid from the enterohepatic circulation (Chiang, 2015). In contrast, several reports showed that LAB ingestion promotes hepatic Cyp7A1 protein expression together with an increase of the efflux as bile acids (Heo et al., 2018; Hu et al., 2013; Qu et al., 2020) It seems that such cholesterol‐reducing mechanism did not occur in this study.…”
Section: Discussioncontrasting
confidence: 87%
“…Therefore, the expression of hepatic Cyp7A1 protein reflects the hepatic cholesterol level and the influx of bile acid from the enterohepatic circulation (Chiang, 2015). In contrast, several reports showed that LAB ingestion promotes hepatic Cyp7A1 protein expression together with an increase of the efflux as bile acids (Heo et al., 2018; Hu et al., 2013; Qu et al., 2020) It seems that such cholesterol‐reducing mechanism did not occur in this study.…”
Section: Discussioncontrasting
confidence: 87%
“…Although AST did not return to the normal range, the results of the hepatic histological examination revealed that the hepatic fatty degeneration improved, which is consistent with the results reported by Oh and Kim [15,16]. Studies have shown that Lactobacillus can improve hypercholesterolemia in mice by activating Lxr-α in the liver and intestine, thereby enhancing the excretion of fecal cholesterol and bile acid in the small intestine [17]. As a probiotic, in addition to reducing blood lipid, it also has antioxidant and anti-inflammatory effects, which can improve the pathology in chronic low-grade inflammation related to obesity or metabolic syndrome [18,19].…”
Section: Effects Of Lactobacillus In the Liversupporting
confidence: 90%
“…De-conjugation of the bile salts by bacterial bile salt hydrolase (BSH) has been reported as an important mechanism that is physiologically associated with the hypo-cholesterolemic effect of probiotics (Begley et al, 2006; Ha et al, 2006; Park et al, 2007). The WHO has recommended that along with capability for colonization of gastrointestinal (GI) epithelia and resistance to harsh GI conditions, BSH activity should be considered as one of the main criteria for selection of probiotics (FAO/WHO, 2002).…”
Section: Introductionmentioning
confidence: 99%